2015
DOI: 10.4172/2376-127x.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Pesticide Exposure of School Children in Agricultural Villages in Indonesia

Abstract: The effects of environmental chemicals on children's health are important issues in Asian developing countries undergoing rapid urbanization, although little data have been reported. We investigated the organophosphorus (OP) pesticide exposure of 235 elementary school children living in three agricultural villages in the Citarum watershed, Bandung, Indonesia, through urinary and blood biomonitoring. We evaluated four common dialkylphosphate (DAP) metabolites of OP compounds: dimethylphosphate (DMP), dimethylth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…According to the study in Ecuador, Suarez-Lopez et al [14] found AChE of 3.08 ± 0.51 U/ml among children (four to nine years old) living with flower plantation workers. Furthermore, AChE in our study was lower than the study among Indonesia children having age of seven to eight years (3.3 ± 0.5 U/ml) living in agricultural villages [35]. This may be explained by AChE level increasing linearly with the age of children [14].…”
Section: Discussioncontrasting
confidence: 80%
“…According to the study in Ecuador, Suarez-Lopez et al [14] found AChE of 3.08 ± 0.51 U/ml among children (four to nine years old) living with flower plantation workers. Furthermore, AChE in our study was lower than the study among Indonesia children having age of seven to eight years (3.3 ± 0.5 U/ml) living in agricultural villages [35]. This may be explained by AChE level increasing linearly with the age of children [14].…”
Section: Discussioncontrasting
confidence: 80%
“…Spearman's correlations presented that chlorpyrifos concentrations on hands and feet were not significantly associated with blood cholinesterase activities, suggesting that exposure to chlorpyrifos in this study was not sufficiently severe enough to cause overt toxicity that could be detected by AChE. This is similar to a study by Sekiyama (2015) [97].…”
Section: Factors Associated With Blood Cholinesterase Activitiessupporting
confidence: 86%
“…However, no AChE standards exist for children [19]. [97]. This may be explained by AChE level increasing linearly with age of children [19].…”
Section: Blood Cholinesterase Activities Of Young Childrenmentioning
confidence: 99%
“…Research on the level of pesticide residues in agricultural and food commodities as well as in the environment, including soil, water and organisms have been carried out [1][2][3][4][5], including efforts to detoxify. Since chemical pesticides or synthetic discovered and used by many farmers.…”
Section: Introductionmentioning
confidence: 99%